Ardanza remembers - Zubizarreta, José Luis (Razón y fe, 2018)
Every self-respecting politician ends up writing his memoirs. Former president José Antonio Ardanza was not going to be less. In Pasión por Euskadi, in its Spanish version, Euskadi en el corazón, in its Basque version, written both from his nationalist and a democrat position, Ardanza narrates his origins and Basque education, and explains the guidelines that guided his government action and, to the present and future, invites Basque and Spanish society to continue betting more on inclusion than on exclusion